SOSIALISASI PENGOLAHAN AIR DENGAN “WATER MEMBRANE FILTRATION” DARI MATA AIR POLAMAN KEBUMEN - Heri Septya Kusuma; Bambang Sugiarto; Suranto; Retno Dwi Nyamiati (Politeknik Negeri Sriwijaya, 2023)
This community service aims to socialize water treatment technology from the Polaman spring in Polaman, Kebakalan Village, Karanggayam, Kebumen, Central Java, and further enhance the capabilities of UKM partners in processing water into packaged drinking water products and increasing the market value of the water. The Polaman spring is the main water source for the community in that area, but its water quality does not yet meet the safe standards for human consumption. This community service involves the implementation of water treatment technology in several stages. Firstly, an initial survey is conducted to understand the condition of the water source and the needs of the local community. Then, the appropriate water treatment method is chosen based on those conditions and needs. The applied method is filtration technology using microfiltration, ultrafiltration, nanofiltration, and reverse osmosis, complemented with UV radiation. Subsequently, water treatment is socialized by utilizing the filtration technology. Through this water treatment socialization, it is expected that the water quality from the Polaman spring can be improved and deemed safe for local consumption. Additionally, it is also expected to raise public awareness regarding the importance of safe water treatment and responsible water usage.